1980
DOI: 10.1111/j.1365-3083.1980.tb00043.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DR‐like Antigens in the Epithelium of the Human Small Intestine

Abstract: Sections of ethanol-fixed, paraffin-embedded tissue specimens from different parts of the human gastrointestinal tract were stained by an indirect immunofluorescence method with a rabbit antiserum to HLA-DR-antigens from B lymphocytes. A specific staining reaction was seen in a patchy pattern apically in the columnar cells of the normal small intestine, decreasing in intensity from the top of the villi towards the crypts. No HLA-DR-like antigens could be detected in colon or stomach epithelium, whereas cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
64
1

Year Published

1981
1981
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(77 citation statements)
references
References 29 publications
10
64
1
Order By: Relevance
“…In graft-versus-host disease, colonic epithelium of the rat likewise expresses such antigens (Mason et al, 1981). In accordance with Scott et al (1980) and Thompson et al (1982) we found that normal colonic epithelium was virtually negative or only faintly stained with the monoclonal antibody to HLA-DR antigens used in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In graft-versus-host disease, colonic epithelium of the rat likewise expresses such antigens (Mason et al, 1981). In accordance with Scott et al (1980) and Thompson et al (1982) we found that normal colonic epithelium was virtually negative or only faintly stained with the monoclonal antibody to HLA-DR antigens used in this study.…”
Section: Discussionsupporting
confidence: 92%
“…We used a 3-step immunofluorescence technique applied to ethanol-fixed sections. The primary murine monoclonal antibody was directed against a nonpolymorphic determinant and produced the same staining pattern in small intestinal epithelium as that obtained previously in our laboratory by the use of a polyclonal rabbit antiserum to human HLA-DR antigen (Scott et al, 1980). Daar et al (1982) used frozen sections and another monoclonal antibody in a peroxidase-anti-peroxidase technique.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, class II antigens can be expressed on several other cell types under certain conditions. Intestinal, urinary, and other epithelia may express class II antigens, as well as several tumor cells (9,(13)(14)(15)(16)(17)(18)(19)(20)(21). The functional significance of this phenomenon is unknown, although it has been suggested that these cells might also present antigens to T cells (22).…”
Section: Introductionmentioning
confidence: 99%
“…Class II MHC molecu les are also expressed on the basolateral membrane and apical ~urface of mature epithelial cells of th~ small intestine and on the epithelium of Pcyer's patches, but these molecules are not found on stomach or colon epithelial celb unless they are directly associated with lymphoid follicles (8). C lass lI MHC molecules may be involved in the absorption of luminal macromolecules across the epithel ium in a manner analogous ro that suggested for class I MHC type molecules in mediating the uptake of lgG from maternal milk (9,10).…”
Section: Antigen-presenting Cells In the Intestinementioning
confidence: 99%